THE EFFECT OF SERVICE QUALITY AND CUSTOMER SATISFACTION ON REPURCHASE INTENTION AT HONDA MOTOR DEALER TDM NATAR - Agustina, Adelli; Rinova, Dora (Penerbit Lafadz Jaya, 2025)
The objective of this. Research determines the influence between customer satisfaction and service quality, as well as the likelihood of customers making repeat purchases at the Honda Motor TDM Natar dealership. Maintaining high service standards and ensuring customer satisfaction are essential for client retention and encouraging repeat business in the competitive automotive industry. Although previous studies have examined the link between these two factors, this research focuses specifically on Honda Motor dealers in Natar, an area that has not been previously studied. The analysis utilizes SPSS version 30 software to perform a multiple linear regression analysis, employing non-probability sampling methods, particularly purposive sampling. An aggregate of 87 customers of the Honda Motor TDM Natar dealership were surveyed using questionnaires to gather data. The results determine the influence customer satisfaction and service quality.